ROOT WELD METAL IMPACT TOUGHNESS OF AN ENERGY COMPONENT - Julijan Salamunić (Journal of Energy Technology, 2024)
In energy engineering, high-strength low-alloy steels are used for building high-loaded modern constructions. The weakest link of a welded structure is a welded joint at which cracks appear, which can lead to sudden destruction. Thus, the welded joints are made with a high impact toughness that can prevent unstable crack propagation. This research deals with the experimental determination and analysis of Charpy impact toughness curves at the weld root of an energy component for different additive materials.